Integration of specific metrics can promote the understanding of scavenging dynamics - Inagaki, Akino; Allen, Maximilian L.; Koike, Shinsuke (Frontiers in Ecology and Evolution, 2025)
Vertebrate scavenging contributes to key ecosystem functions through the cycling of nutrients from carrion. However, the dynamics of scavenging are complex with many unknowns, necessitating the use of multiple metrics to measure the dynamics within vertebrate scavenger assemblages and the impact of scavenging on ecological systems. We propose a conceptual model representing a series of the scavenging processes that are critical to ecosystem functioning. The model includes 13 key metrics based on 4 primary questions to consider in studies of vertebrate scavenging to explain how scavenging dynamics are related to ecosystem functions. Our model enhances understanding of how scavenging dynamics impact ecosystem functions at different spatial and temporal scales and offers a framework for future studies to refine our understanding of scavenging across different ecosystems.